Patient selection for LIVE therapy: From clinical indications to multimodality imaging individual case planning. Issue 9 (9th September 2021) - Neves, Paulo; Pillay, Thasee; Annest, Lon; van Bladel, Kevin; Kaiser, Erhard; Stahl, Fabian; Hanke, Thorsten; Swaans, Martin; Klein, Patrick; Ruf, Tobias; von Bardeleben, Ralph Stephan
Abstract: Background: Less Invasive Ventricular Enhancement (LIVE) with Revivent TC is an innovative therapy for symptomatic ischemic heart failure (HF). It is designed to reconstruct a negatively remodeled left ventricle (LV) after an anterior myocardial infarction (MI) by plication of the scar tissue. Its indications are specific, and as with any other structural heart intervention, the success of the procedure starts with appropriate patient selection. We aim to present the indications of the technique, crucial aspects in patient selection, and individual case planning approach. Methods and results: After clinical evaluation, transthoracic echocardiography is the first imaging modality to be performed in a potential candidate for the therapy. However, definitive indication and detailed case planning rely on late gadolinium‐enhanced cardiac magnetic resonance imaging or multiphasic contrast‐enhanced cardiac computed tomography. These imaging modalities also assist with relative or absolute contra‐indications for the procedure. Individual assessment is done to tailor the procedure to the specifics of the LV anatomy and location of the myocardial scar. Conclusion: LIVE procedure is a unique intervention to treat symptomatic HF and ischemic cardiomyopathy after anterior MI. It is a highly customizable intervention that allows a patient‐tailored approach, based on multimodality imaging assessment and planification.